RapD Is a Multimeric Calcium-Binding Protein That Interacts With the Rhizobium leguminosarum Biofilm Exopolysaccharide, Influencing the Polymer Lengths - Tarsitano, Julián (2022)
Rhizobium leguminosarum synthesizes an acidic polysaccharide mostly secreted to the extracellular medium, known as exopolysaccharide (EPS) and partially retained on the bacterial surface as a capsular polysaccharide (CPS). Rap proteins, extracellular protein substrates of the PrsDE type I secretion system (TISS), share at least one Ra/CHDL (cadherin-like) domain and are involved in biofilm matrix development either through cleaving the polysaccharide by Ply glycanases or by altering the bacterial adhesive properties. It was shown that the absence or excess of extracellular RapA2 (a monomeric CPS calcium-binding lectin) alters the biofilm matrix’s properties. Here, we show evidence of the role of a new Rap protein, RapD, which comprises an N-terminal Ra/CHDL domain and a C-terminal region of unknown function. RapD was completely released to the extracellular medium and co-secreted with the other Rap proteins in a PrsDE-dependent manner. Furthermore, high levels of RapD secretion were found in biofilms under conditions that favor EPS production. Interestingly, size exclusion chromatography of the EPS produced by the ΔrapA2ΔrapD double mutant showed a profile of EPS molecules of smaller sizes than those of the single mutants and the wild type strain, suggesting that both RapA2 and RapD proteins influence EPS processing on the cell surface. Biophysical studies showed that calcium triggers proper folding and multimerization of recombinant RapD. Besides, further conformational changes were observed in the presence of EPS. Enzyme-Linked ImmunoSorbent Assay (ELISA) and Binding Inhibition Assays (BIA) indicated that RapD specifically binds the EPS and that galactose residues would be involved in this interaction. Taken together, these observations indicate that RapD is a biofilm matrix-associated multimeric protein that influences the properties of the EPS, the main structural component of the rhizobial biofilm.